Isolation of genes related to heterocyclic compound degradation from marine bacteria - Ong, L.H (Universiti Malaysia Sarawak, UNIMAS, 2012)
Dibenzofuran terminal dioxygenase gene or dbfA1 gene and biphenyl dioxygenase gene bphA1 gene are the genes responsible for the first step of aromatic compound metabolism found in various microorganisms to metabolize dibenzofuran and biphenyl respectively. Thalassospira profundimaris strain M01 and Pseudomonas pachastrella strain M03 are the bacteria that had been previously identified to have the capability of degrading biphenyl and dibenzofuran respectively. The purpose of this study is to detect the presence of reported heterocyclic compound degrading genes (bphA1, dbfA1) in these bacteria. Degenerative primers were designed based on the consensus regions of dibenzofuran and biphenyl degrading genes on reported strains. These primers were designed by multiple alignments of genes coding for reported dioxygenases, in order to detect the presence of these genes in bacteria T. profundimaris strain M01 and P. pachastrella strain M03 respectively via PCR. A total of 4 sets of primers were design designated bphA1F1R1, bphA1F2R2, dbfA1F1R1, and dbfA1F2R2 respectively. The primer set dbfA1F2 and dbfA1R2 produced bands on agarose gel with desired size of approximately 1,000 bp indicating the presence of dbfA1 gene.